Application of Sendai framework for disaster risk reduction in food security during flood disaster in Malaysia: a narrative review - Mud Shukri, Muhammad Ikhwan; Azmi, Nazmi Ainaa; Kanthavelu, Chandramalar; Zainal, Nur Za’Imah; Abdul Manaf, Rosliza; Muhamad Saliluddin, Suhainizam (Universiti Putra Malaysia, 2023)
Disaster risk reduction (DRR) plays essential roles in ensuring food security to avoid adverse social, economic and financial implications to the disaster victims. This article aims to review existing DRR strategies in food security during flood disasters and recommend strategies that can be adapted into policies in Malaysia according to the Sendai Framework. Sendai Framework provides comprehensive, globally recognized priority themes in DRR while highlighting governmental and stakeholders’ responsibility. A literature review was carried out by searching available published literatures from online databases and selected information used in this review is taken from articles, journals, reports, national reports, news, and thesis regarding the topic from November 2021 to January 2022. This review revealed that DRR strategies of food security during flood disasters in Malaysia lack one out of 14 work areas in four priorities in the Sendai Framework, which is the national-level risk and vulnerability assessment system and tools. This article proposed 19 recommendations to improve eight work areas across all four priority areas to enhance national food security during flood disasters.